Study of the thermal mode of a barn for piglets and a sow, created by combined heating system - Zhelykh, Vasyl; Dzeryn, Oleksandra; Shapoval, Stepan; Furdas, Yurij; Piznak, Bohdan (Eastern-European Journal of Enterprise Technologies, 2017)
The present research addresses solution to the relevant problem of energy efficient heating supply of pig farms with barns of pigs and a sow by applying combined heating systems based on local heating of places for animal keeping. A physical model is developed, which offered the possibility to carry out a complex of experimental studies on determining temperature mode in the barn for piglets and a sow. We established the patterns of influence of thermal capacity of individual heating devices, in particular the heating panel in the place of sow keeping, as well as the heating mat and the infrared heater, on the thermal condition of specific areas. Assessment of the influence of the main factors of the research on its original characteristics was performed. We obtained the equation for determining relative air temperature in the zone of piglets and sow keeping, which depends on relative height of the operation area at a variable air velocity, as well as on incoming air temperature, influenced by the number of animals and background temperature in the premises. Graphical dependences were constructed and empirical dependences were derived based on the conducted experimental studies that can be used in subsequent engineering calculations. Based on the obtained results, we compiled recommendations on the choice of thermotechnical parameters of heating devices, particularly their geometric dimensions, material and method of location of heating elements.